SYSTEMATIC LITERATUR REVIEW: MEDIA PEMBELAJARAN BERBASIS DIGITAL PADA MATA PEMBELAJARAN IPA - Agti Fiana Qoirul Ananta; Fenita Khairani; Risa Andriyani; Budi Nur Ismail; Fina Fakhriyah; Erik Aditia Ismaya (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
This article aims to analyze: (1) technological advances from time to time that affect learning media in schools, (2) digital media in science subjects. Technology is the result of scientific developments in the world of education, so education should utilize technology to assist and support effectiveness in the implementation of learning. In digital learning media, learning material is presented based on circumstances, situations and events, audio or visual in an interesting and interactive way. In this article the method used is Systematic Review (SR) or what is generally called Systematic Literature Review (SLR) is a systematic technique for collecting, critically testing, integrating and compiling the results of various research studies on research questions or topics of interest. The results of a review of eight journals entitled the use of digital-based media in science subjects obtained an average percentage of 71% and the results showed good feasibility and digital media could be used in the learning process. Overall, technological advances in Indonesia are very influential in the world of education, learning media which are increasingly modified according to technological advances can help make the teaching and learning process better, and students will get to know modern technology from an early age